Handbook of diet, nutrition and the skin - Preedy, Victor R.; SpringerLink (Online service) (Wageningen : Wageningen Academic Publishers, 2012)
Studies have clearly shown that optimal diet and nutrition can prevent skin disease. Moreover, novel nutritional components have been used experimentally to treat skin conditions. However, the clinical application of these nutrients awaits confirmation. It is thus up to health care professionals to present new knowledge in order to provide advice or treatments for skin problems. This handbook provides, in a single volume, comprehensive coverage of the relation between skin and diet and nutrition in its broadest sense. The Handbook of diet, nutrition and the skin consists of sections on general aspects of skin, nutrition and diet, micronutrients, nutraceuticals, cancer and specific skin conditions. Unique features of each chapter in this volume include relevant and useful 'key facts' which highlight interesting or important findings of the specific subjects and 'summary points' that are designed to abstract each chapter in take home messages. This handbook will be of interest to a wide range of readers, such as dermatologists, doctors, nurses and those interested in, or working within the area of skin health. This will of course also include nutritionists and dieticians, dermatologists, cosmetic scientists, health workers and practitioners, college and university lecturers and undergraduate and graduate students.
Introduction -- 1. The skin: an introduction -- General aspects of skin, nutrition and diet -- 2. Gut bacteria and skin health -- 3. The fatty acids and the skin: a focus on the n-6 family of unsaturated fatty acids -- 4. Role of vitamin B6 in skin health and diseases -- 5. Antioxidants and skin: an overview -- Micronutrients -- 6. The skin and vitamin D -- 7. Vitamin C, gene expression and skin health -- 8. Strategies for vitamin E transdermal delivery -- 9. Vitamin E chemistry, biological activity and benefits on the skin -- 10. Dietary tocotrienol and UVB-induced skin damage -- 11. Zinc and skin health: an overview -- 12. Iron and skin health: iron stimulates skin function -- Nutraceuticals and skin -- 13. Skin photoprotection and nutraceuticals: an overview -- 14. Effect of flaxseed- and borage oil ingestion on skin conditions -- 15. Dietary red ginseng and skin protection -- 16. Dietary grape seed proanthocyanidins and skin cancer -- 17. Olive oil as a skin protector -- 18. Protective effect of garlic in skin cancer -- 19. Pre- and probiotics for human skin -- 20. Curcumin (turmeric) and its evolving role in skin health -- 21. Protective effects of vitamin C derivatives on skin atrophy caused by Sod1 deficiency -- Skin cancer, nutrition and diet -- 22. Omega-3 fatty acids and non-melanoma skin cancer -- 23. Skin cancer and folate metabolism -- 24. Vitamin D and skin cancer -- Specific skin conditions in relation to diet and nutrition -- 25. Acne and nutrition -- 26. Food allergy and atopic dermatitis -- 27. Fructo-oligosaccharides and skin inflammation -- Index -- About the editor.
Keywords: Life sciences; Life Sciences; Life Sciences, general